Analysis of Compensation in Increasing Performance of Non-Civil Servant Catholic Instructors at the Ministry of Religion in Gorontalo Province - Reinne Febriana Koraag; Irawaty Igirisa; Hapsawati Taan (Jurnal Ilmu Manajemen dan Bisnis, 2022)
The present study aims to describe and analyze as well as providing the objective overview about giving compensation to Non-Civil Servant Catholic Instructors at the Ministry of Religion in Gorontaloprovince. It also aims to describe and analyze the factors determining the compensation to Non-Civil Servant Catholic Instructors at the Ministry of Religion in Gorontalo province. The results show that the compensation to Non-Civil Servant Catholic Instructors which is based on the aspect of the type of compensation is inadequate, moreover, its system is not effective and its payment is not being paid on time yet. Furthermore, the factors determining the compensation to Non-Civil Servant Catholic Instructors at the Ministry of Religion in Gorontalo province are bids and demand for employees, organizational abilities and willingness, work productivity, education and work experience.